Large Snake Lineup for South Florida - Jenna Cole; Justin Dalaba; Melissa Miller; Frank J. Mazzotti (EDIS, 2021)
Fifty species of native snakes live in Florida, help maintain a balance in the ecosystem, and encourage healthy crops. Many non-native snakes have become established, as well, and some have harmed the ecosystem. This brochure is a guide to identifying the snakes of south Florida and differentiating between non-native and commonly confused native snake species.